DOI: 10.30707/etd2015.dukett.j
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse And Identity Development: The Role Of Attachment And Self-Esteeem

Abstract: The purpose of the study was to examine how childhood sexual abuse (CSA) influences identity development along with attachment and self-esteem. The participants included 208 first-year female undergraduate students from Illinois State University.Students were afforded the opportunity to receive extra credit for their participation and could enter into a random prize drawing. Participants completed a demographics questionnaire, Rosenberg Self-Esteem Scale, The Experiences in Close Relationships Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…the victimization has a presumed damage to the normal psychosocial processes responsible for the development of positive self-esteem, one of the components of selfconcept. Several studies show that victims of child sexual abuse have lower self-esteem than those who are not (Cantón-Cortés et al, 2012;Dukett, 2015;and Kim, Park & Park, 2017). In the study of Hall and Hall (2011), feelings of depression, guilt, shame and self-blame, eating disorders, somatic concerns, anxiety, dissociative patterns, repression, denial, sexual problems, and relationship problems are commonly reported by victims who have been sexually abused.…”
Section: Framework Of the Studymentioning
confidence: 99%
“…the victimization has a presumed damage to the normal psychosocial processes responsible for the development of positive self-esteem, one of the components of selfconcept. Several studies show that victims of child sexual abuse have lower self-esteem than those who are not (Cantón-Cortés et al, 2012;Dukett, 2015;and Kim, Park & Park, 2017). In the study of Hall and Hall (2011), feelings of depression, guilt, shame and self-blame, eating disorders, somatic concerns, anxiety, dissociative patterns, repression, denial, sexual problems, and relationship problems are commonly reported by victims who have been sexually abused.…”
Section: Framework Of the Studymentioning
confidence: 99%
“…Developmental psychology research has suggested that: (1) the core of identity development occurs during childhood (Briere 1992; Josselson 1987; Lieblich et al 2004); (2) victimization during childhood, such as childhood sexual abuse, can profoundly and adversely affect identity development (Dukett 2015; Martsolf and Draucker 2008); and, (3) individuals with a history of childhood sexual abuse can have identities characterized by victimization, where “the world and the self are viewed through the lens of the victimized child” (Philips and Daniluk 2004, p. 177). In light of this past work, it seemed possible that a history of childhood sexual abuse (CSA) could predispose individuals, when subsequently diagnosed with cancer as adults, to adopt a cancer victim identity.…”
Section: Introductionmentioning
confidence: 99%